Conflicts : the poetics and politics of Palestine-Israel - Mor, Liron (Fordham University Press, 2024)
Conflicts engages Hebrew and Arabic literature to critically reassess the concept of conflict, both in Palestine-Israel and in general. Drawing on a diverse archive, ranging from the 1930s to the present and from prose and poetry to film and television, it reveals indigenous literary concepts that better theorize the region's antagonisms and mediations, its colonial technologies and anticolonial practices.